Variations in antibiotic resistance genes and microbial community in sludges passing through biological nutrient removal and anaerobic digestion processes in municipal wastewater treatment plants. (February 2023) - Raza, Shahbaz; Kang, Kyeong Hwan; Shin, Juhee; Shin, Seung Gu; Chun, Jihyun; Cho, Hyun Uk; Shin, Jingyeong; Kim, Young Mo
Abstract: Antimicrobial resistance (AMR) represents a relentless, silent pandemic. Contributing to this are wastewater treatment plants (WWTPs), a potential source of antibiotic resistance genes' (ARGs) transmission to the environment, threatening public health. The presence of ARGs in pathogenic bacteria and their release into the environment by WWTPs threatens the public health. The current study investigated changes in ARGs' abundance in biological nutrient removal (BNR) processes and anaerobic digestion (AD) reactors of two WWTPs. Also, microbial community structure, which is known to shape the distribution and abundance of ARGs, was also analyzed. The relative abundance of eight ARGs ( tet X, tet A, tet M, TEM, sul 1, sul 2, erm B and qnr D) was quantified as ARGs' copies/16 S rRNA gene copies using quantitative polymerase chain reaction (qPCR). Microbial community composition was assessed by 16 S rRNA microbiome sequencing analysis. Tet X was prevalent among the eight ARGs, followed by TEM and sul 1. However, its abundance was decreased in the AD sludges compared to BNR sludges. Proteobacteria was the major bacterial phylum found in all the sludge samples, while Arcobacter, 12up and Acidovorax were the predominant genera. Acinetobacter and Flavobacterium were significantly more abundant in the BNR sludges, while 12up and Aeromonas were predominant in AD sludges. Principal component analysis (PCA) revealed a clear difference in dominant ARGs and bacteria between the sludges in the processes of BNR and AD of the two WWTPs. Clinically relevant bacterial genera, Klebsiella and Enterococcus, found in both the BNR and AD sludges, were significantly correlated with the tet X gene. Throughout this study, the relationship between microbial communities and specific ARGs was revealed, illustrating that the composition of the microbial community could play a vital role in the abundance of ARGs. These results will better inform future studies aimed at controlling the spread of ARGs and their potential hosts from WWTPs. Graphical abstract: Image 1 Highlights: Tet X was predominant in biological nutrient removal (BNR) sludges. Amount of tet M was higher in anaerobic digestion (AD) sludge than in BNR sludges. Abundance of tet X was lower in AD sludges than in BNR sludges. Enterococcus and Klebsiella were positively correlated with tet X in both sludges. BNR and AD sludges had different dominant ARGs and bacteria.